ohpikhâwasiw: kiskeyihtamowin âcimowin: She Raises the Children: Sharing Our Knowledges from Stories - St-Denis, Natalie; Favel, Janis; Moore, Joanna; Walsh, Christine (Journal of the Motherhood Initiative for Research and Community Involvement, 2022)
The stories we braid within this article bring together narratives of Indigenous mothering, which highlight the importance of culture and kinship to support the healthy development, safety, and wellbeing of our children. In our motherwork, we resist colonial forces and counter child welfare practices and the profession of social work, which enforce Eurocentric parenting and enact racist policies that continue to remove Indigenous children from their families at a disproportionate rate—a continuation of assimilationist tactics and genocide of Indigenous peoples enacted during the residential school era, the Sixties Scoop, and ongoing genocidal policies. Our braided stories provide a counternarrative—one of resistance in (re)claiming Indigenous mothering, stories of resiliency in (re)webbing kinship systems and stories of hope in (re)membering our cultural identities. In (re)claiming, (re)connecting, and (re)webbing, we acknowledge being in different places in our journey of Indigenous mothering. Some of us have been born into the web of our kinship systems, whereas others have been on a journey of reattaching the threads to reassemble the intricate web of kinship, culture, and community. In the spirit of reconciliation and the decolonization of child welfare practices, our work serves as a counternarrative—liberating our realities from the dominant negative stereotypes imposed by colonial systems and oppressive forces—and provides insight into the power of Indigenous mothering. Indigenous mothering provides the love and nurturing, as well a web of kinship, that support and establish life-long relationships that will sustain the wellbeing, resurgence, and prosperity of our families and communities.